Systematizing the lexicon of platforms in information systems: a data-driven study - Bartelheimer, Christian; zur Heiden, Philipp; Lüttenberg, Hedda; Beverungen, Daniel (Electronic Markets)
Abstract While the Information Systems (IS) discipline has researched digital platforms extensively, the body of knowledge appertaining to platforms still appears fragmented and lacking conceptual consistency. Based on automated text mining and unsupervised machine learning, we collect, analyze, and interpret the IS discipline’s comprehensive research on platforms—comprising 11,049 papers spanning 44 years of research activity. From a cluster analysis concerning platform concepts’ semantically most similar words, we identify six research streams on platforms, each with their own platform terms. Based on interpreting the identified concepts vis-à-vis the extant research and considering a temporal perspective on the concepts’ application, we present a lexicon of platform concepts, to guide further research on platforms in the IS discipline. Researchers and managers can build on our results to position their work appropriately, applying a specific theoretical perspective on platforms in isolation or combining multiple perspectives to study platform phenomena at a more abstract level.
Keywords: Management of Technology and Innovation; Marketing; Computer Science Applications; Economics and Econometrics; Business and International Management

Schärfung der Sinne. Josef Winklers Mikroästhetik im Kontext kleiner Prosaformen der Moderne - Öhlschläger, Claudia (Inter- und transmediale Ästhetik bei Josef Winkler)

Evaluating database systems relying on secure multiparty computation - Anonymous, A

Cost of Privacy-preserving SMPC Protocols for NN-Based Inference - Anonymous, A

Alfred Anderschs "Die Rote" mit Antonioni gelesen - Öhlschläger, Claudia (Das Italien des Alfred Andersch. Interkulturelle und intermediale Konstellationen)

Lattice Revocation Mechanisms - Lohse, Jan

Selective area heteroepitaxy of InAs nanostructures on nanopillar-patterned GaAs(111)A - Riedl, Thomas; Kunnathully, Vinay S.; Verma, Akshay Kumar; Langer, Timo; Reuter, Dirk; Büker, Björn; Hütten, Andreas; Lindner, Jörg (Journal of Applied Physics)
A process sequence enabling the large-area fabrication of nanopillar-patterned semiconductor templates for selective-area heteroepitaxy is developed. Herein, the nanopillar tops surrounded by a SiN x mask film serve as nanoscale growth areas. The molecular beam epitaxial growth of InAs on such patterned GaAs[Formula: see text]A templates is investigated by means of electron microscopy. It is found that defect-free nanoscale InAs islands grow selectively on the nanopillar tops at a substrate temperature of 425 °C. High-angle annular dark-field scanning transmission electron microscopy imaging reveals that for a growth temperature of 400 °C, the InAs islands show a tendency to form wurtzite phase arms extending along the lateral [Formula: see text] directions from the central zinc blende region of the islands. This is ascribed to a temporary self-catalyzed vapor–liquid–solid growth on [Formula: see text] B facets, which leads to a kinetically induced preference for the nucleation of the wurtzite phase driven by the local, instantaneous V/III ratio, and to a concomitant reduction of surface energy of the nanoscale diameter arms.
Keywords: General Physics and Astronomy

Size‐Dependent Strain Relaxation in InAs Quantum Dots on Top of GaAs(111)A Nanopillars - Riedl, Thomas; Kunnathully, Vinay; Trapp, Alexander; Langer, Timo; Reuter, Dirk; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: Mechanical Engineering; Mechanics of Materials

Democracy ≠ Democracy. Creating digital infographics to compare different democratic systems. - Janzen, Thomas (Englisch betrifft uns)

Geschlechtsidentität - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Sexuelle Orientierung - Krämer, Anike (Fachlexikon der Sozialen Arbeit)

Qualifizierung von Studierenden des Grund- und Förderschullehramts für Inklusion in Schule und Unterricht - Franzen, Katja; Albers, Timm; Hellmich, Frank (Qualifizierung für Inklusion. Grundschule)
Inklusion ist als Thema aus dem deutschen Bildungssystem nicht mehr wegzudenken und trotzdem stellt sie weiterhin eine Herausforderung auf unterschiedlichen Ebenen dar. Die Qualifizierung der pädagogischen Fachkräfte ist dabei neben der Bereitstellung adäquater Rahmenbedingungen als ein besonders wichtiges Handlungsfeld zu betrachten. Die Bände der Reihe „Qualifizierung für Inklusion“ greifen den bestehenden Forschungs- und Entwicklungsbedarf auf und geben einen Überblick über die Ergebnisse der vom BMBF im Rahmen des Programms „Qualifzierung der pädagogischen Fachkräfte für inklusive Bildung“ geförderten Forschungsprojekte. Adressiert werden damit sowohl Wissenschaftler:innen als auch mit dem Themenfeld Inklusion befasste Personen und Institutionen der Aus-, Fort- und Weiterbildung, der Bildungsadministration und der Bildungspolitik. Der zweite Band der Reihe versammelt die Vorstellung von Projekten, Ergebnissen und Materialien, die sich dem Bildungsbereich der Grundschule zuordnen lassen. Die Reihe besteht aus drei weiteren Bänden, in denen die Ergebnisse zur Qualifizierung für Inklusion im Elementarbereich (Band 1), in der Sekundarstufe (Band 3) sowie in der Berufsschule, Hochschule und Erwachsenenbildung (Band 4) vorgestellt werden.

Primary School Principals’ Views on the Required Conditions for a Successful Implementation of Inclusive Education - Görel, Gamze; Hellmich, Frank (Australasian Journal of Special and Inclusive Education)
Abstract Following the United Nations Convention on the Rights of Persons With Disabilities, questions concerning the joint education of students with and without special educational needs remain to be answered. Currently, there is a need for knowledge about the necessary conditions for a successful implementation of inclusive education. Thus, the aim of the present study is to identify conditions for the implementation of inclusion that are seen as necessary by primary school principals. Therefore, 32 primary school principals were interviewed. The results of the interview study reveal that factors like personnel, financial and material resources as well as building infrastructure in primary schools are seen as important requirements for the successful realisation of inclusive education. Apart from that, the importance of attitudes towards inclusion and sociopolitical conditions for the realisation of inclusion became apparent. Further conditions, which are mentioned from the interviewed principals’ point of view, are related to teacher training, appropriate class sizes and, for example, opportunities for exchanging information. The results of the study indicate that there are essential obstacles as perceived by primary school principals that can impede the implementation of inclusion in primary schools.
Keywords: General Engineering

Qualität der Erfahrungen aus dem inklusiven Unterricht und Selbstwirksamkeitsüberzeugungen von Grundschullehrkräften - Franzen, Katja; Moschner, Barbara; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

Adaptiver Unterricht in der (inklusiven) Grundschule aus der Perspektive von Lehrkräften - Löper, Marwin Felix; Hellmich, Frank (Sonderpädagogik – zwischen Dekategorisierung und Rekategorisierung)

FRIEND-SHIP Intervention Program – The Handbook - Aroni, Katerina; Toulia, Anastasia; Alves, Sílvia Regina Gonçalves; Hassani, Sepideh; Heidrich, Franziska Anna; Franzen, Katja; Görel, Gamze; Löper, Marwin Felix; Aguiar, Teresa; Silveira-Maia, Mónica; Sanches-Ferreira, Maria Manuela Pires Sanches; Hellmich, Frank; et al.

Der Rollenhut als Vermittlungsmedium - Rollenklärungsprozesse im Kontext multiprofessioneller Kooperationen als Thema universitärer Aus- und Fortbildungen von Lehrkräften und Sozialpädagog*innen - Neumann, Phillip; Hopmann, Benedikt; Lütje-Klose, Birgit (Herausforderung Lehrer*innenbildung - Zeitschrift zur Konzeption, Gestaltung und Diskussion)
Multiprofessionelle Kooperation zwischen allgemeinen und sonderpädagogischen Lehrkräften und mit weiteren Fachkräften, u.a. der Schulsozialarbeit, der Schulpsychologie und mit Schulbegleitungen, gilt bei der Entwicklung inklusiver Schulen als zentrale Stellschraube. Dementsprechend wird Kooperation im Kontext Schule auch in der universitären Ausbildung von zukünftig miteinander kooperierenden Professionen sowie in Fortbildungen für Lehrkräfte und multiprofessionelle Teams verstärkt ins Blickfeld gerückt. Zugleich lässt sich beobachten, dass in inklusiven Schulen bislang vermeintlich klare Zuständigkeiten, insbesondere zwischen Sonder- und Sozialpädagog*innen, aufweichen und neu austariert werden müssen. Bei der Entwicklung multiprofessioneller Teams gilt die Klärung von Rollen und Aufgaben als eine besondere Herausforderung, wenn unterschiedliche Professionen mit unterschiedlichen institutionellen Anbindungen und pädagogischen Zielperspektiven oder Grundhaltungen mitei-nander kooperieren. Das vorgestellte Instrument – der Rollenhut – dient dazu, in multiprofessionellen Gruppen eine individuelle Reflexion über die eigenen Aufgaben anzustoßen und auf dieser Grundlage gemeinsam über die gegenseitigen Erwartungen und Rollen zu diskutieren. Das Instrument wurde im Kontext von Fortbildungen multiprofessioneller Teams an Schulen konzipiert und auch im Rahmen der universitären Lehrer*innenbildung erprobt.

Teachers Between a Rock and a Hard Place: Goal Conflicts Affect Teaching Motivation Mediated by Basic Need Satisfaction - Gorges, Julia; Neumann, Phillip; Störtländer, Jan Christoph (Frontiers in Psychology)
Teaching is a highly demanding profession that requires handling multiple and potentially contradictory goals. Therefore, it is likely that teachers experience conflict between work-related goals on a daily basis. Intraindividual goal conflict may occur when individuals pursue multiple goals drawing on the same limited resources (resource-based goal conflict), or when two or more goals are incompatible in terms of goal attainment strategy or desired end states (inherent goal conflict). Because goal conflict is typically associated with negative effects such as attenuated motivation and wellbeing, teacher goal conflict may jeopardize teaching motivation. This cross-sectional study investigated the effects of in-service teachers’ ( N = 302) goal conflicts on their autonomous (intrinsic and identified regulation) and controlled (introjected and extrinsic regulation) teaching motivation and tested the satisfaction of teachers’ basic need for autonomy, competence, and relatedness as mediators. In line with our hypotheses, results from structural equation modeling showed that frequently experiencing resource-based goal conflict leads to a lower satisfaction of the basic need for autonomy, which, however, was unrelated to teaching motivation. In contrast, frequently experiencing inherent goal conflict attenuates the satisfaction of the basic need for competence, which, in turn, positively predicted autonomous teaching motivation and negatively predicted extrinsic regulation. As expected, relatedness was not associated with the experience of goal conflict. The discussion focuses on differential effects of the two types of goal conflict on teaching motivation and on the relevance to expand research on teachers’ intraindividual goal conflicts.
Keywords: General Psychology

Bielefelder Fortbildungskonzept zur Kooperation in inklusiven Schulen (BiFoKi) : Technical Report V. 1.0 - Gorges, Julia; Neumann, Phillip; Wild, Elke; Lütje-Klose, Birgit; Grüter, Sandra; Weber, Antonia; Senior, Jonathan

High‐Resolution Study of Changes in Morphology and Chemistry of Cylindrical PS‐ b ‐PMMA Block Copolymer Nanomasks during Mask Development - Bürger, Julius; Venugopal, Harikrishnan; Kool, Daniel; de los Arcos de Pedro, Maria Teresa; Gonzalez Orive, Alejandro; Grundmeier, Guido; Brassat, Katharina; Lindner, Jörg (Advanced Materials Interfaces)
Keywords: General Medicine